2021
DOI: 10.1021/acsomega.1c03434
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromogenic Detection of Live Bacteria Using Soluble and Insoluble Prussian Blue

Abstract: Microbial detection is crucial for the control and prevention of infectious diseases, being one of the leading causes of mortality worldwide. Among the techniques developed for bacterial detection, those based on metabolic indicators are progressively gaining interest due to their simplicity, adaptability, and, most importantly, their capacity to differentiate between live and dead bacteria. Prussian blue (PB) may act as a metabolic indicator, being reduced by bacterial metabolism, producing a visible color ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Furthermore, from the plots of A 775 against the concentration of W­(V) in Table , the molar absorption coefficient for the IVCT transition between W­(V) and W­(VI) is evaluated to be 6.85 × 10 3 dm 3 mol –1 cm –1 according to the Lambert-Beer law (Figure S4). Our data indicate that the IVCT transition between the photogenerated W­(V) and W­(VI) in WO 3 has a molar absorption coefficient close to that of Prussian Blue. , …”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, from the plots of A 775 against the concentration of W­(V) in Table , the molar absorption coefficient for the IVCT transition between W­(V) and W­(VI) is evaluated to be 6.85 × 10 3 dm 3 mol –1 cm –1 according to the Lambert-Beer law (Figure S4). Our data indicate that the IVCT transition between the photogenerated W­(V) and W­(VI) in WO 3 has a molar absorption coefficient close to that of Prussian Blue. , …”
Section: Resultsmentioning
confidence: 54%
“…Our data indicate that the IVCT transition between the photogenerated W(V) and W(VI) in WO 3 has a molar absorption coefficient close to that of Prussian Blue. 10,11 ■ CONCLUSIONS…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PrBl has recently been used in the design of a variety of portable or wearable analytical devices, all of which were further modified with enzymes, and enzymatic reduction of PrBl to Prussian white (PrWh) was detected amperometrically [ 22 , 23 , 24 ]. Furthermore, ferricyanide is a common metabolic indicator for both Gram-positive and Gram-negative bacteria, and recent studies have shown that PrBl can be reduced to PrWh through the metabolic activity of a variety of microorganisms, including E. coli , a feature that has been used to design electrochromic sensors for bacteria [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous bacterial species are vital for improving safety and quality of life across several fields, including drug discovery, food production, sewage treatment, and energy harvesting; however, some bacteria are harmful. Bacterial tests, such as those performed in various areas, including food, medical, and environmental research, must meet requirements for sensitivity, selectivity, speed, and cost. In recent years, much research has been actively conducted on the development of bacterial tests, whose principles range from luminescence, , absorption, , or current response-based detections to the combination of microscopy or spectroscopy and deep learning. While these developments have many benefits in terms of sensitivity, selectivity, speed, and cost, they require sufficient development time to replace traditional methods.…”
mentioning
confidence: 99%